Headhunting and the body in Iron Age Europe - Armit, Ian (Cambridge University Press, 2012)
Across Iron Age Europe the human head carried symbolic associations with power, fertility status, gender, and more. Evidence for the removal, curation and display of heads ranges from classical literary references to iconography and skeletal remains. Traditionally, this material has been associated with a Europe-wide 'head-cult', and used to support the idea of a unified Celtic culture in prehistory. This book demonstrates instead how headhunting and head-veneration were practised across a range of diverse and fragmented Iron Age societies. Using case studies from France, Britain and elsewhere, it explores the complex and subtle relationships between power, religion, warfare and violence in Iron Age Europe
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Alltag, Brauchtum; Headhunters / Europe; Human body / Symbolic aspects / Europe; Human remains (Archaeology) / Europe; Rites and ceremonies / Europe; Violence / Europe; Iron age / Europe; Verehrung; Eisenzeit; Kopfjäger; Kopf; Europa; Europe / Social life and customs; Europe / Religious life and customs